The Role of E-WOM Emotionality on Gen Z’s Purchase Intention in E-Commerce - Dwi Martiyanti; Rahmayana, Fadina (Journal of Marketing Innovation (JMI), 2024)
The growing trend of online shopping among Generation Z has led to a significant reliance on consumer reviews, which are often perceived as more objective than corporate marketing messages. However, reviews do not always directly translate into purchase intentions. The originality of this study lies in its focus on Generation Z, a cohort that, according to a 2022 survey, is more inclined to read customer reviews before making online purchases. This research contributes to a deeper understanding of how the emotional aspects of e-WOM influence Generation Z's purchase intentions in e-commerce. The study specifically examines the impact of e-WOM, emotional attachment, and trust on Generation Z's purchase intentions within the e-commerce context. Utilizing a convenience sampling method, the study collected data from 162 respondents and analyzed it using SMARTPLS 4.0. The findings reveal that e-WOM, emotional attachment, and trust all significantly influence Generation Z's purchase intentions in e-commerce. These insights are valuable for marketers, highlighting the importance of e-WOM emotionality as a critical tool for enhancing the purchase intentions of Gen Z consumers.